2021
DOI: 10.1080/14693062.2021.1922340
|View full text |Cite
|
Sign up to set email alerts
|

A green COVID-19 recovery of the EU basic materials sector: identifying potentials, barriers and policy solutions

Abstract: This paper explores climate-friendly projects that could be part of the COVID-19 recovery while jump-starting the transition of the European basic materials industry. Findings from a literature review on technology options in advanced development stages for climate-friendly production, enhanced sorting, and recycling of steel, cement, aluminium, and plastics, are combined with insights from interviews with 31 European stakeholders in these sectors about the practical and economic feasibility of these technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…However, the performed analysis aims to obtain the enablers' ranking and all the enablers have obtained different values. Besides the topmost and the least, remaining enablers are ranked as E9 3 and Table 9), which establishes that; the inception of green innovations (E9) is a major projected demand to emerge from the concern of negative environmental issues which aligns with the framework projected by Chiappinelli et al (2021) and stands upfront to industrial symbiosis/synergy (E10).…”
Section: Resultsmentioning
confidence: 92%
“…However, the performed analysis aims to obtain the enablers' ranking and all the enablers have obtained different values. Besides the topmost and the least, remaining enablers are ranked as E9 3 and Table 9), which establishes that; the inception of green innovations (E9) is a major projected demand to emerge from the concern of negative environmental issues which aligns with the framework projected by Chiappinelli et al (2021) and stands upfront to industrial symbiosis/synergy (E10).…”
Section: Resultsmentioning
confidence: 92%
“…More detail is required on the design of industrial policies to determine whether recent commitments mark a substantively new approach. Strategic support will need to address decarbonisation alongside financial stability (Chiappinelli et al, 2021). There are several policy tools which could be pursued to strategically decarbonise the steel sector, falling under the following strands: 1) driving deployment of available and novel technologies; 2) promoting material efficiency across the value chain; 3) addressing embodied emissions through standards; 4) developing effective business models; 5) defining a regional approach to the sector; and 6) considering the value of sectoral carbon budgets.…”
Section: Strategies and Policies For Sustainable Steelmentioning
confidence: 99%
“…Energy-intensive industries, including iron and steel, cement, chemicals and petrochemicals, pulp and paper, and aluminium, account for 25–33% of carbon emissions and 38% of total final energy use worldwide ( Allwood et al., 2010 ; IEA, 2017 ). These basic material-producing industries are mostly considered hard to decarbonize ( Chiappinelli et al., 2021 ). Several innovative technologies already exist to significantly reduce emissions in these sectors ( Bataille et al., 2018 ; IEA, 2017 ), compatible with the net-zero pathways announced worldwide, including by the European Union.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, policies for renewable energies have demonstrated that de-risking such investments via revenue-stabilizing policy frameworks can lead to lower carbon mitigation costs, via better financing conditions ( Egli et al., 2018 , May and Neuhoff, 2021 ). Design options of CCfDs have been discussed in several policy reports ( Gerres and Linares, 2020 n.d.; Hauser et al., 2021 ; Lösch et al., 2021 ; Neuhoff et al., 2019 ; Sartor and Bataille, 2019 ), including in the form of a project-specific put option ( McWilliams and Zachmann, 2021 ), and several research articles reference CCfDs as a useful part of a policy toolbox ( Chiappinelli et al., 2021 ; Löfgren and Rootzén, 2021 ; Muslemani et al., 2021 ; Sutherland, 2020 ). Vogl.…”
Section: Introductionmentioning
confidence: 99%